Gambaran Pengetahuan Remaja Puteri Tentang Anemia Di SMA Negeri 1 Perhentian Raja Kabupaten Kampar Tahun 2023 - Putri, Del Arifka; Harahap, Dewi Anggriani; Syahda, Syukrianti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Anemia often occurs in society, especially teenagers, anemia in teenage girls is still quite high, according to WHO, the prevalence of anemia in teenage girls is 30%, while the incidence of anemia in teenage girls in Indonesia aged 15-24 years is 32.0%. The prevalence of anemia in Riau among adolescents aged 15-24 years is 25.1%. The aim of the research is to find out how knowledge about the definition, symptoms, impact and prevention of anemia in young women at SMA Negeri Perhentian Raja is described. This research is a descriptive research. The research was conducted on 20-22 September 2023 with a sample size of 298 young women at SMA Negeri 1 Perhentian Raja using the Total Sampling technique. The research instrument used a questionnaire sheet with univariate data analysis of frequency distribution. The research results showed that 180 (60.4%) people were in the good category understanding the definition of anemia, 167 (56%) were in the good category regarding understanding the symptoms of anemia, 158 (53%) people were in the poor category regarding understanding the impact of anemia, 152 (51%) were in the poor category regarding understanding of anemia prevention, 161 (54%) were in the poor category regarding Fe tablets and 162 (54.4%) were in the poor category regarding anemia knowledge. It is hoped that respondents will increase their knowledge about the definition, symptoms, impacts and ways to prevent anemia by reading or listening to information from trusted sources or following counseling.